The Role of Islamic Education Teachers in Improving the Character of Nationalism in Boarding School - Muhammad Anas Ma`arif; Muhammah Husnur Rofiq (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2018)
The emergence of radicalism and violence in the name of religion has flourished even has penetrated the territory of educational institutions. Therefore, the importance of the role of Islamic education teachers in guarding the character of peace love is necessary, peace love/nationalism can be enhanced through Islamic education and not only become the burden of civic education teachers. Thus this research is important to do. Purpose-This study aims to explain and develop the role of Islamic education teachers in improving the character of student nationalism. Design/methodology-This research uses library research by collecting some related books and journals to analyze the content of the role of Islamic education teachers in improving student nationalism. Findings-The role of Islamic education teachers in improving student nationalism can be through; the internalization of the value of nationalism into the school culture, the integration of nationalism in the learning of Islamic education. Originality/Value-The character of nationalism is not only shaped by citizenship education teachers but can be through Islamic education teachers. understanding Islam in its entirety will automatically lead to peaceful love behavior.